STUDI VIABILITAS Lactobacillus plantarum FNCC-0027 PADA SARI BUAH APEL (Malus sylvestris Mill) DENGAN VARIETAS YANG BERBEDA - Ardhian, Kahfi; Kartika, I Desak Putu; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p10, 2019)
The purpose of this research was to know the viability of Lactobacillus plantarum FNCC-0027 in apple juice with different varieties. This research is an experimental research. Viability data of L.plantarum FNCC-0027 on apple juice of Manalagi variety, Anna, and Romebeauty was described. Data from the analysis before and after fermentation by L.plantarum FNCC-0027 on each apple juice tested using paired T Test at a = 5%. The total of LAB from the three apple varieties decreased from 10 5 CFU/ml to 10 4 CFU/ml with a decrease by 1 log CFU/ml. The addition of L.plantarum FNCC-0027 gave a significant effect in total of sugar, total of acidity, and pH of three apple varieties. Anna's apple juice has the lowest decrease of total LAB after 48 hours fermentation with the final result is 0,63 x 10 4 CFU/ml, total of sugar 0,95%, total of acidity 0,44%, and pH 3,55% . Keywords : Lactobacillus plantarum FNCC-0027 , variety of apple juice, LAB viability